TRADISI NGANTAT SALIN DALAM ERA MODERNISASI PADA MASYARAKAT DESA ULAK KERBAU BARU KECAMATAN TANJUNG RAJA KABUPATEN OGAN ILIR - Khairani (Program Studi Sejarah Peradaban Islamm UIN Raden Fatah Palembang, 2024)
The Ngantat Salin tradition is a tradition carried out by the people of Ulak Kerbau Baru Village before the wedding, nowadays it is still carried out even though it has changed over time. This research aims to find out the form of change in the Ngantat Salin tradition in weddings in the village of Ulak Kerbau Baru, as well as the factors causing it. By using qualitative research methods, and data collection techniques through observation, interviews. As well as analysis techniques with data reduction, data presentation and verification. The results of the research show that the changes that occurred in the Ngantat Salin tradition occurred in the form of Copy that was given, namely that it was more numerous and varied than in the past. In the past, it was in the form of kuntung, pillows, mats, serindak, as well as shrimp paste, tamarind, and onions. Nowadays it is no longer used but uses other types of salt such as rice, salt, soy sauce, oil, eggs, fruit, cakes, toiletries, prayer equipment, make-up equipment. In the past, only two people represented its implementation, but nowadays it has become busy and is being participated by many people. Factors causing this change include advanced formal education, economic conditions in society, era factors, and cultural influences from other regions.